Non-invasive treatment of Clostridioides difficile infection with a human-origin probiotic cocktail through gut microbiome-gut metabolome modulations - Gurung, Bijay; Courreges, Maria C.; Pollak, Julie; Malgor, Ramiro; Jiang, Lin; Wang, Bo; Wang, Shaohua (Frontiers in Microbiology, 2025)
Clostridioides difficile (C. difficile) is a leading cause of hospital-associated diarrhea, primarily due to gut dysbiosis following antibiotic use. Probiotics have been found to provide several benefits to hosts via modulation of the gut microbiota and their metabolites. However, till now, no conventional probiotics have been clearly proven to be an effective prophylactic option for CDI prevention. Therefore, more studies on developing specific probiotic candidates targeting CDI and improving diversity of probiotics administrated are needed. In this study, a human-origin highly diverse and highly targeted probiotic cocktail (Pro11) containing 11 various probiotic species was developed against C. difficile. Pro11 protected mice against CDI with lower clinical scores and higher survival rates, and inhibited C. difficile in vivo with less C. difficile burden and toxins production determined in colon. Histological analysis demonstrated that Pro11 strengthened gut barrier, reducing gut permeability (less secreted sCD14 in serum) and gut inflammation. In addition, gut microbiome analysis demonstrated that Pro11 increased gut microbiome diversity and beneficial species. Along with gut microbiome modulation, gut metabolites including butyrate, were significantly increased in the probiotics-fed group. Results from this study highlighted probiotics as a promising CDI therapy as gut microbiota modulators, which will lay the foundation for translating probiotics in mitigating CDI and other intestinal pathogens for clinical use.